Vitamin D Deficiency and Allergic Rhinitis in Children: A Narrative Review - Javad Ghaffari; Alireza Ranjbar; Annegret Quade (Mazandaran University of Medical Sciences, 2015)
Context: Allergic diseases such as allergic rhinitis (AR) and immune-mediated inflammatory diseases are the most common chronic diseases among children. Although the cause of AR has yet to be clearly identified, genetic and environmental factors are known to play an important role in the development of the disease. Evidence Acquisition: In a more recent classification, AR is categorized as intermittent and permanent. Vitamin D has a known and important role in the absorption of calcium and preservation of bone density. The prevalence of vitamin D deficiency in children is reported to be between 30% and 50% in the world. Vitamin D confers the growth and development of the immune system including the development of regulatory T cells. Results: Two-thirds of the reviewed articles show a correlation between serum levels of vitamin D and allergic diseases, while the reaming ones demonstrate no correlation between vitamin D and AR and some even report a rise in the incidence of AR following the use of vitamin D supplement. Conclusions: It seems that further clinical trials and meta-analytic studies are necessary to confirm this correlation. The present study aimed at reviewing vitamin D deficiency in children with AR.